Java 7 recipes a problem-solution approach - Juneau, Josh; Dea, Carl; Guime, Freddy; O'Conner, John (The expert's voice in Java, 2012)
Java 7 Recipes offers solutions to common programming problems encountered every day while developing Java-based applications. Fully updated with the newest features and techniques available, Java 7 Recipes provides code examples involving Servlets, Java FX 2.0, XML, Java Swing, and much more. Content is presented in the popular problem-solution format: Look up the programming problem that you want to solve. Read the solution. Apply the solution directly in your own code. Problem solved!